IEEE Information Theory Workshop 2010 (ITW 2010) 2010
DOI: 10.1109/itwksps.2010.5503143
|View full text |Cite
|
Sign up to set email alerts
|

Some bounds on the capacity of communicating the sum of sources

Abstract: We consider directed acyclic networks with multiple sources and multiple terminals where each source generates one i.i.d. random process over an abelian group and all the terminals want to recover the sum of these random processes. The different source processes are assumed to be independent. The solvability of such networks has been considered in some previous works. In this paper we investigate on the capacity of such networks, referred as sum-networks, and present some bounds in terms of min-cut, and the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 23 publications
(17 reference statements)
0
27
0
Order By: Relevance
“…4) Linear Coding: Another popular achievable strategy is linear coding where each intermediate node forwards a linear combination of the incoming symbols. For general directed graphs, when the function to be computed is linear, random linear coding is known to be optimal [33]. In [17], it is shown that linear coding is insufficient when the function to be computed is nonlinear and the potential loss due to employing linear coding is quantified.…”
Section: Fig 1: Multi-session Examplementioning
confidence: 99%
See 3 more Smart Citations
“…4) Linear Coding: Another popular achievable strategy is linear coding where each intermediate node forwards a linear combination of the incoming symbols. For general directed graphs, when the function to be computed is linear, random linear coding is known to be optimal [33]. In [17], it is shown that linear coding is insufficient when the function to be computed is nonlinear and the potential loss due to employing linear coding is quantified.…”
Section: Fig 1: Multi-session Examplementioning
confidence: 99%
“…For linear function computation with a single terminal, linear coding is known to be optimal [33], but the case of multiple terminals has not been studied.…”
Section: B Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is known that for single-receiver networks, linear coding is sufficient for solvability when computing a scalar linear target function [4], [16]. Analogous to the coding capacity for network coding, the notion of computing capacity was defined for network computing in [8] and is the supremum of achievable rates of computing the network's target function.…”
mentioning
confidence: 99%